2019
DOI: 10.1186/s12882-019-1406-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structure and function after revascularization versus medical therapy for renal artery stenosis: the ASTRAL heart echocardiographic sub-study

Abstract: Background The ASTRAL trial showed no difference in clinical outcomes between medical therapy and revascularization for atherosclerotic renal vascular disease (ARVD). Here we report a sub-study using echocardiography to assess differences in cardiac structure and function at 12 months. Methods ASTRAL patients from 7 participating centres underwent echocardiography at baseline and 12 months after randomisation. Changes in left ventricular ejection fraction (LVEF), left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[102][103][104][105] However, 2 major prospective randomized clinical trials, the Angioplasty and Stenting for Renal Artery Lesions (ASTRAL, 806 patients 53 ) and the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL, 947 patients 106 ), clearly demonstrated that renal angioplasty and stenting did not confer a significant benefit for the prevention of clinical events when added to comprehensive medical therapy. Although a significant proportion of patients included had only modest stenoses, 107 the data revealed added substantial risks by the intervention with limited evidence of clinical benefit in terms of hypertension or recovery of renal function.…”
Section: Revascularization Strategiesmentioning
confidence: 97%
“…[102][103][104][105] However, 2 major prospective randomized clinical trials, the Angioplasty and Stenting for Renal Artery Lesions (ASTRAL, 806 patients 53 ) and the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL, 947 patients 106 ), clearly demonstrated that renal angioplasty and stenting did not confer a significant benefit for the prevention of clinical events when added to comprehensive medical therapy. Although a significant proportion of patients included had only modest stenoses, 107 the data revealed added substantial risks by the intervention with limited evidence of clinical benefit in terms of hypertension or recovery of renal function.…”
Section: Revascularization Strategiesmentioning
confidence: 97%